New Challenges in Compressed Matter Physics: Future Research Projections - Zhang Wei; Shanshan Xu; Murphy Xavier (Journal of Tecnologia Quantica, 2024)
Compressed Matter Physics has become an increasingly important field in understanding the properties of matter under extreme conditions, such as those found inside giant planets, neutron stars, and in experiments with ultra-intense lasers. However, although there has been progress in the understanding of compressed matter, there are still major challenges that need to be overcome in understanding the behavior of matter under these extreme conditions. This research aims to explore new challenges in the physics of compressed matter and identify future research projections that can overcome these challenges as well as to improve understanding of the properties of matter under extreme conditions and develop potential applications in various fields, including astronomy, nuclear physics, and materials engineering. This research method involves analysis of the latest literature in the field of compressed matter physics, as well as discussion and collaboration with experts in the scientific community. The results show that there are several major challenges in understanding the physics of compressed matter, including a deeper understanding of the behavior of matter at very high pressures and temperatures, as well as the development of more sophisticated technologies to measure and model these extreme conditions. In addition, we also identify several future research projections that can address these challenges, including the development of new experimental techniques, the development of more sophisticated theoretical models, and the use of more powerful energy sources to achieve extreme conditions. higher. The conclusions of this study highlight the importance of continuing to explore the world of compressed matter to understand the properties of matter under extreme conditions. By identifying key challenges and future research projections, we hope to inspire continued research in this field and advance understanding of the universe at extreme scales.